Hollywood Highbrow : From Entertainment to Art - Baumann, Shyon, 1971- (Book collections on Project MUSE., 2007)
"In Hollywood Highbrow, Shyon Baumann tells how social and cultural forces radically changed the public's perceptions of American movies just as those forces were radically changing the movies themselves." "The development in the United States of an appreciation of film as an art was, Baumann shows, the product of large changes in Hollywood and American society as a whole. With the postwar rise of television, American movie audiences shrank dramatically and Hollywood responded by appealing to richer and more educated viewers. Around the same time, European ideas about the director as artist, an easing of censorship, and the development of art-house cinemas, film festivals, and the academic field of film studies encouraged the idea that some American movies - and not just European ones - deserved to be considered art."--Jacket